IMPLEMENTASI PROGRAM POSYANDU LANSIA UNTUK MENJAGA KESEHATAN LANJUT USIA - Darmin Tuwu; La Tarifu (Journal Publicuho, 2023)
Elderly people are people who fall into the category of the age group sixty years and over. This old age group is increasing day by day. They are vulnerable to mental and spiritual health problems, so it is necessary to make a Posyandu program for the elderly. This qualitative research with a case study approach is about the Integrated Service Post Program (Posyandu) which is given to the elderly age group to maintain the health and quality of life of the elderly. The object of study is the elderly who can still walk to the local Posyandu. Methods of collecting data through observation, interviews, and documentation. The main source of reference was obtained through literature studies related to the Posyandu program for the elderly. The results of the study found that the Elderly Posyandu program was carried out once a month, which was located at the local village head office or at a place determined by the residents. The service programs provided by the Posyandu for the elderly to the elderly are such as: health services, providing additional food, sports activities, and non-health activities such as spiritual activities, social gathering, productive economic activities, distribution of hobbies, and social interaction with fellow elderly. Through this activity, the elderly receive health and social benefits, so that the health and quality of life of the elderly can be well maintained